Study on cutting performance and tool wear of micro-textured tool for milling Ti6Al4V - Shen Xiang-yu; Guo Xu-hong; Deng Da-song; Lu Li-li; Chen Ya-dong (Functional Materials, 2017)
The research found that the surface texture applied to the cutting tool could improve the frictional states of tool-chip and tool-workpiece effectively. In order to study the technology of surface texture how to effect the cutting performance of the integral end milling cutter for cutting titanium alloy (Ti6AlV).The longitudinal grooves, lateral grooves and pits were prepared by laser processing technique on the rake face of milling tool made of YG6X, which was to explore the cutting performance of non-texture tools and texture tools under the condition of dry and lubrication. As the results, compared with the non-textured tools, the longitudinal micro-groove and micro-pit could effectively reduce the milling force, increase the chip curl and improve the anti-sticking properties of the tool, thereby the oxidation wear, adhesive wear of the rake face and the abrasion wear of the flank face were alleviated as well. The experimental results demonstrated that the milling force of the tool with longitudinal micro-groove was reduced by 62% and the width of wear on rake face was reduced by 68%, the wear width on the flank face of the micro-pits tool was decreased by 42.6%.The direction of micro-groove on the tool’s rake face had a great influence on the anti-sticking properties, and the tools with longitudinal micro-grooves had the best anti-sticking property. The fine medium played a major role in improving the friction between the tool-chip friction pairs.